Efficacy of Inquiry-based Science Laboratory Work in Human Physiology Lesson at Lower Secondary Level and Lower Cycle of Grammar School - Rokos, Lukáš; Vomáčková, Vladislava (Scientia in educatione, 2017)
The main aim of this study was a comparison of inquiry-based science education (IBSE) and traditional science lab courses where students perform selected human physiology assignments listed in a manual they have received from the teacher. This paper presents the results of a study assessing IBSE impact on the students’ knowledge and skills acquisition of lower secondary school pupils and students at grammar school lower cycle. One pre-test and two post-tests were administered in order to assess and compare the respective levels of their knowledge and skills. The results of the grammar school lower cycle students indicated a statistically significant improvement, unlike those of the lower secondary level pupils. IBSE had demonstrably positive impact on the grammar school students, particularly in the skill-oriented part of the tests.